2018
DOI: 10.1155/2018/7868531
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dental Bleaching with Whitening Dentifrices: A Systematic Review

Abstract: A systematic review was performed to evaluate whether whitening toothpastes promote tooth whitening when compared to the use of conventional (nonbleaching) dentifrices. This review was registered at PROSPERO (CRD42017065132) and is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Electronic systematic searches of PubMed/MEDLINE, Scopus, and the Cochrane Library were conducted for published articles. Only randomized clinical trials in adults that compared the use of so-called whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 17 publications
1
22
0
11
Order By: Relevance
“…Historically, one of the main components in toothpastes used for whitening has been abrasives, which help to eliminate extrinsic stains as well as prevent their formation. A wide range of other components is usually added to this abrasive system, such as surfactants, calcium chelators, polymers and enzymes; however, evidence indicates that the abrasive is the most crucial component in the toothpastes for stain removal 11, 12 . Yet, there are worldwide governing limitations on the maximum levels of abrasives allowed in any toothpaste and thus there is some restrictions to how much whitening can be effectively and (most importantly) safely obtained through abrasive advancements 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, one of the main components in toothpastes used for whitening has been abrasives, which help to eliminate extrinsic stains as well as prevent their formation. A wide range of other components is usually added to this abrasive system, such as surfactants, calcium chelators, polymers and enzymes; however, evidence indicates that the abrasive is the most crucial component in the toothpastes for stain removal 11, 12 . Yet, there are worldwide governing limitations on the maximum levels of abrasives allowed in any toothpaste and thus there is some restrictions to how much whitening can be effectively and (most importantly) safely obtained through abrasive advancements 8 .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 The ΔE* ab values have often been used in tooth bleaching studies to indicate the perceptible tooth color changes after treatment. 3,7,11,34 Recently, studies reported that ΔE 00 showed better correlation with visual perception than ΔE* ab, 21,23,26 mainly for the interaction between chroma and hue differences in the blue region and a modification in the a* coordinate, which is important for colors with low chroma (neutral colors). 40 In this study, color changes were calculated using CIELab and CIEDE2000 formulas, and it was not detected significant difference for ΔE* ab or ΔE 00 among the CT and WT groups.…”
Section: Discussionmentioning
confidence: 99%
“…Δ E * ab measures the variability in color between objects of the same size, shape and is represented by the combination of three coordinates ( L *, a *, and b *) 38,39 . The Δ E * ab values have often been used in tooth bleaching studies to indicate the perceptible tooth color changes after treatment 3,7,11,34 . Recently, studies reported that Δ E 00 showed better correlation with visual perception than Δ E * ab, 21,23,26 mainly for the interaction between chroma and hue differences in the blue region and a modification in the a * coordinate, which is important for colors with low chroma (neutral colors) 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a temporary filling is performed and the patient can be sent home. After two or three days, the patient must go back to the clinic, where the dentist will check the degree of whitening obtained and evaluate the need to carry out another application [27]. Protocols for tooth bleaching of non-vital teeth are various and follow strict directions in order to avoid side effects, such as external absorption of the root.…”
Section: Discussionmentioning
confidence: 99%